2011
DOI: 10.1186/1477-7827-9-112
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian sensitivity index is strongly related to circulating AMH and may be used to predict ovarian response to exogenous gonadotropins in IVF

Abstract: BackgroundSerum anti-Mullerian hormone (AMH) is currently considered the best marker of ovarian reserve and of ovarian responsiveness to gonadotropins in in-vitro fertilization (IVF). AMH assay, however, is not available in all IVF Units and is quite expensive, a reason that limits its use in developing countries. The aim of this study is to assess whether the "ovarian sensitivity index" precisely reflects AMH so that this index may be used as a surrogate for AMH in prediction of ovarian response during an IVF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 14 publications
5
48
0
1
Order By: Relevance
“…Our results confirmed the previous findings [5] that OSI was strongly and significantly correlated with AMH and AFC, which were suggested in meta-analyses as the best predictors of ovarian responsiveness as defined on oocyte number [6,7]. There was also significant correlation of OSI with age and body mass index, the latter being not demonstrable in the previous study [5].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results confirmed the previous findings [5] that OSI was strongly and significantly correlated with AMH and AFC, which were suggested in meta-analyses as the best predictors of ovarian responsiveness as defined on oocyte number [6,7]. There was also significant correlation of OSI with age and body mass index, the latter being not demonstrable in the previous study [5].…”
Section: Discussionsupporting
confidence: 92%
“…There was also significant correlation of OSI with age and body mass index, the latter being not demonstrable in the previous study [5]. It conforms to the common understanding that advanced age and overweight/obesity are negative factors affecting ovarian responsiveness [10].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Since the study population was composed of women with prognostic variables that suggested a high responsiveness to ovarian stimulation, a very low cancellation rate (1.5 %) was a priori estimated. Secondary outcomes were the following: total gonadotropin dose, follicular phase length, ovarian sensitivity index (OSI0exogenous FSH/retrieved oocyte) [15], fertilization rate (FR), pregnancy rate (PR) per started cycle, per OPU and per embryo transfer (ET), implantation rate (IR) and live birth rate (LBR) with fresh embryos; pregnancy rate per started cycle, per OPU and per ET, implantation rate and live birth rate with thawed oocytes; cumulative fresh-plusthaw pregnancy rate (CPR).…”
Section: Power Calculationmentioning
confidence: 99%